Can “Characteristic Town” construction protect the rural environment and enhance the rural economy? Perspectives on efficiency improvement and economies of scale - Guangsi Zhang; Xian Chen; Qiang Hu (Humanities & Social Sciences Communications)
Abstract Rural revitalization is a long-term strategy aimed at fostering high-quality economic development. In the context of new urbanization, characteristic towns are pivotal in advancing this goal. Utilizing 169 county-level panel data and county-scale DMSP/OLS nighttime lighting data from 2012 to 2020, this study empirically investigates the policy impact of “Characteristic Town” on rural revitalization in Sichuan Province using the DID method. The findings indicate that the pilot policy of the “Characteristic Town Construction Action” significantly promotes rural revitalization, a conclusion that remains robust after employing the instrumental variables method and conducting a series of robustness tests. Mechanism analysis reveals that the “Characteristic Town” policy fosters rural revitalization by enhancing productivity and promoting population agglomeration. Additionally, heterogeneity analysis shows that the policy’s impact is more pronounced in areas with higher economic development potential and spatial scaling advantages. Further analysis confirms that the “Characteristic Town” policy not only bolsters economic levels but also supports the sustainable development of the rural environment, thus achieving the dual goals of economic strength and ecological preservation.